Impact of externally forced changes on temperature extremes - Morak, Simone (The University of Edinburgh, 2013)
This thesis investigates changes in temperature extremes between 1950-2005, analysing gridded data sets of observations and climate model simulations. It focuses on changes in the frequency of extreme temperatures occurring in single days or over periods of six or more consecutive days. The study aims to quantify the significance of changes in extreme temperature events and answer the following questions. Are external or human-induced forcings together with natural forcings responsible for the observed change in temperature extremes or can these changes be explained due to natural climate variability alone? Are the observed changes consistent with those from climate model simulations? And are the changes in extremes linked only to changes in the mean climate, or only to those in climate variability or both? The analysis concentrates on changes from global to regional scale and from annual mean to seasonal scale. A detection method is applied to assess if changes are significantly different with respect to the internal climate variability. Results show that there has been a significant increase in warm daily extremes and a decrease in cold ones, both on large and small spatial scales. The increase in warm extremes has been found to be highly correlated with the increase in mean temperature. The changes in daily extremes are well represented in climate model simulations. Changes in the persistent extremes show a detectable increase in the frequency of warm and a decrease in cold events and are reproducible by models.
Keywords: temperature extremes; detection; Climate Change